2022
DOI: 10.1038/s41380-022-01897-w
|View full text |Cite
|
Sign up to set email alerts
|

Brain ageing in schizophrenia: evidence from 26 international cohorts via the ENIGMA Schizophrenia consortium

Abstract: Schizophrenia (SZ) is associated with an increased risk of life-long cognitive impairments, age-related chronic disease, and premature mortality. We investigated evidence for advanced brain ageing in adult SZ patients, and whether this was associated with clinical characteristics in a prospective meta-analytic study conducted by the ENIGMA Schizophrenia Working Group. The study included data from 26 cohorts worldwide, with a total of 2803 SZ patients (mean age 34.2 years; range 18–72 years; 67% male) and 2598 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 66 publications
3
22
1
Order By: Relevance
“…A recent study 52 showed that early antipsychotic medication use might reduce the brain age gap in patients with first-episode schizophrenia. In contrast, the illness duration of the participants was longer in our study (mean: 15.56 years, ranging from 0 to 38 years), and our result showed a lack of association between medication and the brain age gap, which is consistent with the previous studies 17,18,23 . Therefore, we speculate that the brain age gap may be more sensitive to first-episode schizophrenia patients with early medication use but less sensitive to chronic schizophrenia patients with antipsychotic medication use.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A recent study 52 showed that early antipsychotic medication use might reduce the brain age gap in patients with first-episode schizophrenia. In contrast, the illness duration of the participants was longer in our study (mean: 15.56 years, ranging from 0 to 38 years), and our result showed a lack of association between medication and the brain age gap, which is consistent with the previous studies 17,18,23 . Therefore, we speculate that the brain age gap may be more sensitive to first-episode schizophrenia patients with early medication use but less sensitive to chronic schizophrenia patients with antipsychotic medication use.…”
Section: Discussionsupporting
confidence: 91%
“…Chen et al also found that the normalized predicted age difference did not show a significant correlation with the duration of illness in schizophrenia 23 . We found that previous studies had inconsistent results on the association between the brain age gap and duration of illness in individuals with schizophrenia 14,17,21,22 . The relevant studies are still limited.…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations